Management of Stress Resilience at Work Place: The Evolutionary Genetics of Dark Triad Personality - Bidhu Bhusan Mishra, Shakti Ranjan Mohapatra, Deepak Kumar Sahu (Journal of Informatics Education and Research, 2023)
Stress is defined as a physical, chemical or emotional factor that causes bodily or mental tension and may be an aspect in disease causation. It is also described as a state resulting from a stress; especially one of bodily or mental strain emanating from factors that tend to alter an existing equilibrium. Stress is a necessary and common problem associates with human life. It has very undesirable consequences in the emotional, mental and physical well-being of an individual which leads to decreased quality of life and poor organisational performance. People have personality traits that make disagreeable or difficult to deal with them. They may be volatile, arrogant or domineering. Apart from this, other behaviours and characteristics can be seriously damaging and displays toxic combination of these traits and can undermine his colleagues in lasting way and can potentially poison and destroy a team. The present study is focused on “Dark Traid” personality theory. Psychologists have identified three different traits of "Dark Triad" theory i.e. Narcissism, Machiavellianism and psychopathy. The study is mainly descriptive in nature and will explore the three elements of the Dark Triad and identify the behaviors associated with each of them. Also, it explains how they might impact the workplace and create work stress.